Applied Psychology Readings Selected Papers from Singapore Conference on Applied Psychology, 2017 (Springer Singapore, 2018)
This book is a compilation of the best papers presented at the 2017 edition of the Singapore Conference of Applied Psychology (SCAP), an event held annually in Singapore. Discussing the latest innovations, trends, concerns, practical challenges encountered and the solutions adopted in the field of applied psychology, it is a valuable resource for academics, researchers and practitioners wishing to keep themselves up to date with the state of the art in the field.